THE EFFECT OF USING HERO QUEST STRATEGY TOWARD THE STUDENTS’ WRITING SKILL OF RECOUNT TEXT AT TENTH GRADE OF STATE SENIOR HIGH SCHOOL 2 KUOK KAMPAR REGENCY - Asilestari, Putri (Jurnal Pendidikan Tambusai, 2018)
This research was carried out based on researcher’s preliminary study at State Senior High School 2 Kuok at tent grade in academic year 2016/2017. In this research, the researcher use quasi experimental research with post test only. The aim of this research is to find out the effectiveness of the use Hero Quest Strategy in teaching writing skills on recount text. The researcher took two classes as the samples were class X1 as thecontrol group and class X 2 as the experimental class. Total sampling technique was used by the researcher to take the sample. The technique of data collection was test. Meanwhile, to analyze the data, the researcher used Independent Samples T-test formula by using SPSS 20.0 Version. Based on the analysis data the result showed that the average student post test in experimental class were 72.47, and in control class has average students post test were 54.31.The researcher used T-test, the result of the average test calculating (T-test) 0.000. It was proved that this research was 0.000 <0.05. Finally, the researcher concluded that alternative hypothesis (Ha) was accepted and null hypothesis (H0) was rejected. After calculating effect size, it was obtained that there was a small effect size (0.025). It was conclude that H0 is rejected and Ha is accepted. In other words, there is a significant effect of using hero quest strategy on students writing skill of recount text of the tenth grade at state senior school 2 Kuok.